Retrospective cohort study: stereotactic aspiration of necrotic tissue versus conservative medical management for malignant MCA infarction - Zhang, Xi; Zhang, Yao; Chen, Quan; Wu, Hang; Deng, Yijun; Zheng, Aidong; Zhang, Hongtian; Chen, Maogang (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to investigate the efficacy and safety of stereotactic aspiration of necrotic brain tissue in patients aged 61 years and older with malignant middle cerebral artery infarction (MMI).MethodsA total of 121 MMI patients aged 61 years and older were enrolled retrospectively in this cohort. They were subjected to conservative medical treatment alone or in addition to stereotactic aspiration of necrotic brain tissue between 24 and 72 h after symptom onset. Perioperative outcomes and 6-month follow-up outcomes were observed and evaluated.ResultsBaseline characteristics were well balanced between the conservative treatment group and the aspiration group, except for a higher prevalence of hypertension in the conservative group. The incidence of early cerebral herniation (8.5% vs. 47.3%, χ2 = 179.797, P < 0.001) and death (19.1% vs. 64.9%, χ2 = 24.110, P < 0.001) in the aspiration group was significantly lower than that in the conservative group, and there was no significant difference in the incidence of cerebral hemorrhage and intracranial infection between the groups (P > 0.05). At 6-month follow-up, compared with the conservative treatment group, the aspiration group had a higher proportion of patients achieving favorable outcome (mRS 0–3) (25.5% vs. 2.7%, χ2 = 14.641, P < 0.001) and survival without severe disability (mRS 0–4) (55.3% vs. 17.6%, χ2 = 18.755, P < 0.001). Univariable analysis of factors affecting unfavorable outcome (mRS 4–6) showed that the proportion of patients treated with medical therapy alone was significantly higher in the unfavorable outcome group compared to those treated with aspiration(67.3% vs. 32.7%, χ2 = 14.641, P < 0.001). Multivariate binary logistic regression analysis, used to adjust for confounding factors such as atrial fibrillation, diabetes, smoking, GCS and NIHSS scores at 24 h after onset, revealed that treatment with aspiration was an independent factor associated with a 6-month favorable outcome in the elderly patients with MMI (OR 51.713, 95% CI 5.029–531.748, P < 0.001). As a sensitivity analysis, ordinal logistic regression showed that the proportional odds ratio (POR) for the conservative group vs. the aspiration group was 6.737 (95% CI: 3.181–14.271, P < 0.001) in the univariable model and 11.290 (95% CI: 4.827–26.409, P < 0.001) in the multivariable model, confirming that conservative treatment was significantly associated with worse mRS outcomes.ConclusionThe study showed stereotactic aspiration of necrotic brain tissue could be effective and safe for the elderly patients with MMI.